Bi‐ventricular repair of double outlet left ventricle: Experience and review of the literature. Issue 8 (11th July 2020) - Raja, Javid; Menon, Sabarinath; Ramanan, Sowmya; Dutta Baruah, Sudip; Devarakonda, Bhargava V.; Gopalakrishnan, Arun; Dharan, Baiju S.
Abstract: Background: Double‐outlet left ventricle (DOLV) is a rare congenital cardiac anomaly. The aorta and the main pulmonary arterial trunk arises predominantly from the left ventricle and is associated with a malaligned ventricular septal defect, various degrees of hypoplasia of the right ventricle, and presence, or absence of pulmonary stenosis. Bi‐ventricular repair is the preferred treatment option whenever possible. Multiple techniques for bi‐ventricular repair have been described. The best option for DOLV correction is by translocating the pulmonary root from the left ventricle to the right ventricle. In this series, we report four patients who underwent biventricular repair of DOLV with excellent outcomes. Methods: This is a retrospective study of four patients who underwent surgical correction of DOLV between January 2014 and December 2018. We collected all patient details from the institute patient record system. Echocardiographic data were obtained from the records. Intraoperative charts were reviewed for further information on the surgical procedure and cardiopulmonary bypass. Postoperative data included survival, functional status, and followup echocardiography. Results: Of the four children, three underwent pulmonary root translocation, and one child underwent a Reparation al etage Ventriculaire (REV) procedure. There was no mortality in our series, and all children are in a stable clinical condition in the recent follow‐up, and no re‐operations or interventions were required following primary surgical correction. Conclusion: DOLV is anatomically and surgically a challenging subset. Pulmonary root translocation in this anatomy is technically challenging but safe and superior option when compared to other alternative surgical procedures. Pulmonary root translocation can be performed with excellent results, even in infants.